Integrating fishers' knowledge research in science and management. (16th March 2016) - Stephenson, Robert L.; Paul, Stacey; Pastoors, Martin A.; Kraan, Marloes; Holm, Petter; Wiber, Melanie; Mackinson, Steven; Dankel, Dorothy J.; Brooks, Kate; Benson, Ashleen
Abstract: Fishers' knowledge research (FKR) aims to enhance the use of experiential knowledge of fish harvesters in fisheries research, assessment, and management. Fishery participants are able to provide unique knowledge, and that knowledge forms an important part of "best available information" for fisheries science and management. Fishers' knowledge includes, but is much greater than, basic biological fishery information. It includes ecological, economic, social, and institutional knowledge, as well as experience and critical analysis of experiential knowledge. We suggest that FKR, which may in the past have been defined quite narrowly, be defined more broadly to include both fishery observations and fishers "experiential knowledge" provided across a spectrum of arrangements of fisher participation. FKR is part of the new and different information required in evolving "ecosystem-based" and "integrated" management approaches. FKR is a necessary element in the integration of ecological, economic, social, and institutional considerations of future management. Fishers' knowledge may be added to traditional assessment with appropriate analysis and explicit recognition of the intended use of the information, but fishers' knowledge is best implemented in a participatory process designed to receive and use it. Co-generation of knowledge in appropriately designed processes facilitates development and use of fishers' knowledge and facilitates the participation of fishers in assessment and management, and is suggested as best practice in improved fisheries governance.